MODEL PENYELESAIAN PEMBIAYAAN BERMASALAH DENGAN MENGGUNAKAN METODE RESTRUKTURISASI PEMBIAYAAN AKAD MUDHARABAH DI BANK SULSELBAR CABANG SYARIAH MAKASSAR - cakra cakra; Haslinda Haslinda (Fakultas Ekonomi dan Bisnis Islam IAIN Bone, 2021)
Abstract This research discusses aboutsettlement of non-performing financing using the restructuring method and the procedure for granting a restructuring policy for mudrabah contract financing provided by the bank of sulselbar to defaulted customers. The type of research conducted by the researcher is classified as qualitative descriptive with a phenomenological approach. The resources in the research are the leadership of the Islamic Bank Sulselbar along with the front liners as the credit analysis team. With data collection methods in the form of interviews, documentation and several institutional references. Data management and analysis techniques were carried out by in-depth interviews with informants. After doing the research, the writer made the results of the interview by playing back the interview recording and then rewriting the words that matched what was in the recording. After the researchers wrote the results of the interviews, the researchers then made data reduction by way of abstraction, namely taking data that was in accordance with the research context and ignoring data that were not needed. The results show that the problem financing settlement model at the Islamic Bank Sulselbar uses 3 stages, namely financing restructuring, subrogation or guarantor institutions as well as litigation and guarantee execution which are carried out persuasively to customers while still based on applicable regulations. With the procedure for providing a restructuring policy for mudharabah contract financing, it refers to BI regulations as the central bank and still follows the company operating standards (SOP) run by the Islamic Bank of South Sulawesi. Key words: Financing Restructuring, Mudharabah Agreement, BI and OJK